Conceptual framework of acute care nurse practitioner role enactment, boundary work, and perceptions of team effectiveness. (27th May 2012) - Kilpatrick, Kelley; Lavoie‐Tremblay, Mélanie; Lamothe, Lise; Ritchie, Judith A.; Doran, Diane
Abstract Aim. This article describes a new conceptual framework for acute care nurse practitioner role enactment, boundary work and perceptions of team effectiveness. Background. Acute care nurse practitioners contribute positively to patient care by enacting an expanded scope of practise. Researchers have found both positive and negative reactions to the introduction of acute care nurse practitioners in healthcare teams. The process of role enactment, shifting role boundaries, and perceptions of team effectiveness has been studied disparately. A framework linking team structures and processes to desirable outcomes is needed. Data sources. Literature was obtained by searching CINAHL, PsycInfo, MedLine, PubMed, British Nursing Index, Cochrane Library, JSTOR Archive, Web of Science, and Google Scholar from 1985–2010. A descriptive multiple‐case study was completed from March 2009–May 2009. Discussion. A new conceptual framework describing how role enactment and boundary work affect perceptions of team effectiveness was developed by combining theoretical and empirical sources. The framework proposes proximal indicators used by team members to assess their team's performance. Implications for nursing. The framework identifies the inter‐related dimensions and concepts that different stakeholders need to consider when introducing nurse practitioners in healthcare teams. Further study is needed to identify team‐level outcomes that reflect the contributions of all providers to quality patient care, and explore the patients' and families' perceptions of team effectiveness following the introduction of acute care nurse practitioners. Conclusion. The new framework can guide decision‐making and research related to the structures, processes, and outcomes of nurse practitioner roles in healthcare teams.